ZSM-5 molecular sieve, preparation method and application thereof, and catalytic cracking method of triisopropylbenzene

The ZSM-5 molecular sieve with a cross-assembled flaky nanocrystal morphology addresses diffusion and catalytic performance issues, offering improved catalytic performance and diffusion properties through a unique crystal structure and silicon-aluminum ratio.

CN119143145AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310715999.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

Existing ZSM-5 molecular sieves face issues such as poor catalytic performance due to diffusion resistance, limited silicon-aluminum ratio, and challenges in controlling acidity, which affect their effectiveness in organic conversion reactions.

Method used

A ZSM-5 molecular sieve with a unique crystal morphology composed of cross-assembled flaky nanocrystals, featuring rotational symbiosis of 90°±10° and 30°±5°, is synthesized using a specific structure directing agent, allowing for improved accessibility and a wide silicon-aluminum ratio.

Benefits of technology

The modified ZSM-5 molecular sieve exhibits enhanced catalytic performance and diffusion properties, with a high specific surface area and wide silicon-aluminum ratio, suitable for organic conversion reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143145A_ABST
    Figure CN119143145A_ABST
Patent Text Reader

Abstract

The invention relates to the field of molecular sieves, and discloses a ZSM-5 molecular sieve, a preparation method and application of the ZSM-5 molecular sieve, and a catalytic cracking method of triisopropylbenzene. Adjacent sheet-shaped nanocrystals in the molecular sieve have an aggregate crystal morphology formed by cross assembly of sheet-shaped nanocrystals which are in rotational symbiosis at 90 degrees + / -10 degrees and in rotational symbiosis at 30 degrees + / -5 degrees.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular sieves, and in particular to a ZSM-5 molecular sieve and a preparation method and application thereof, and a catalytic cracking method of triisopropylbenzene. Background Art

[0002] The ZSM-5 molecular sieve with MFI structure has a three-dimensional pore structure, and the folded pores along the a-axis have a smaller pore size. The straight channels along the b-axis are larger Therefore, the diffusion rate of molecules in different channels is different, and shortening the b-axis can effectively slow down the influence of diffusion resistance on catalytic performance. Ryoo et al. synthesized MFI zeolite nanosheets using amphiphilic structure-directing agents, introduced mesopores / macroporations, and greatly improved diffusion performance and acid site accessibility [RyongRyoo et al., Science, 333 (6040); Ryong Ryoo et al., Chem. Mater., 2011, 23, 5131-5137]. However, the use of amphiphilic structure-directing agents leads to a reduction in the range of zeolite acid concentration, and it is often impossible to synthesize molecular sieves with higher Si / Al. At the same time, there are also problems such as expensive structure-directing agents, low crystallinity of molecular sieves, low acid strength and hydrothermal stability, and low synthesis yield.

[0003] Xiao and Rimer et al. used small molecule quaternary ammonium salt templates and template-free methods, respectively, to synthesize nanosheet ZSM-5 molecular sieves, but there are still problems such as narrow silicon-aluminum ratio window and difficult to control acidity in catalytic applications [Feng-Shou Xiao et al., J. Am. Chem. Soc., 2022, 144, 14, 6270-6277; Jeffrey D. Rimer et al., Adv. Mater., 2021, 33, 2100897]. Summary of the invention

[0004] The purpose of the present invention is to overcome the mass transfer difficulties of ZSM-5 molecular sieves in the prior art, such as the problem of poor catalytic performance in organic conversion reactions, and to provide a ZSM-5 molecular sieve and its preparation method and application, and a catalytic cracking method of triisopropylbenzene. The ZSM-5 molecular sieve has good accessibility and is used for organic conversion reactions, such as having good catalytic performance when used for catalytic cracking reactions of triisopropylbenzene.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a ZSM-5 molecular sieve, wherein the ZSM-5 molecular sieve has a crystal morphology of agglomerates composed of cross-assembly of flaky nanocrystals, and adjacent flaky nanocrystals in the molecular sieve have a crystal morphology of agglomerates composed of cross-assembly of flaky nanocrystals with rotational symbiosis of 90°±10° and 30°±5°.

[0006] The second aspect of the present invention provides a method for preparing the ZSM-5 molecular sieve according to the first aspect of the present invention, wherein the preparation method comprises: crystallizing a raw material mixture containing a silicon source in the presence of a structure directing agent, wherein the structure directing agent contains a structural unit a represented by formula (1),

[0007]

[0008] In formula (1), X is a halogen ion or a hydroxide ion, and * represents a bonding site.

[0009] The third aspect of the present invention provides the use of the ZSM-5 molecular sieve described in the first aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.

[0010] The fourth aspect of the present invention provides a method for catalytic cracking of triisopropylbenzene, wherein the method comprises: in the presence of the ZSM-5 molecular sieve described in the first aspect of the present invention and / or the hydrogen-type ZSM-5 molecular sieve after hydrogen-modification of the ZSM-5 molecular sieve described in the first aspect of the present invention as an active component, triisopropylbenzene is subjected to a catalytic cracking reaction.

[0011] Compared with the prior art, the present invention has at least the following beneficial effects:

[0012] The ZSM-5 molecular sieve of the present invention has a crystal morphology of an agglomerate composed of adjacent flaky nanocrystals cross-assembled by 90°±10° rotational symbiosis and 30°±5° rotational symbiosis. The crystal morphology is special, the accessibility is good, and the catalytic performance for organic matter conversion reaction is good. The molecular sieve of this morphology has a high specific surface area and a wide range of silicon-aluminum ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is the X-ray diffraction pattern of the molecular sieve sample in Example 1;

[0014] Figure 2 is the N of the molecular sieve sample in Example 1 2 Physical adsorption diagram;

[0015] Figure 3 is the X-ray diffraction pattern of the molecular sieve sample in Example 2;

[0016] Figure 4 is the X-ray diffraction pattern of the molecular sieve sample in Example 3;

[0017] Figure 5 is a SEM image of the molecular sieve sample in Example 3;

[0018] Figure 6 is the X-ray diffraction pattern of the molecular sieve sample in Example 4;

[0019] Figure 7 is the X-ray diffraction pattern of the molecular sieve sample in Example 5;

[0020] Figure 8 is a SEM image of the molecular sieve sample in Example 5;

[0021] Fig. 9 is a SEM image of the molecular sieve sample of the molecular sieve sample in Comparative Example 1;

[0022] Fig.10 This is a SEM image of the molecular sieve sample of the molecular sieve sample in Comparative Example 2. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The first aspect of the present invention provides a ZSM-5 molecular sieve, wherein the ZSM-5 molecular sieve has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and adjacent flaky nanocrystals in the molecular sieve have an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals with rotational symbiosis of 90°±10° and 30°±5°.

[0025] In the present invention, adjacent flaky nanocrystals in the molecular sieve have agglomerates composed of cross-assembly of flaky nanocrystals with 90°±10° rotational symbiosis and 30°±5° rotational symbiosis, and have a special crystal morphology and good accessibility, which can be beneficial to the diffusion of raw materials and their products, and have good catalytic performance in organic matter conversion reactions.

[0026] According to the present invention, in some preferred embodiments, the number of agglomerates of crystal morphologies composed of cross-assembly of 90°±10° rotational intergrowth and 30°±5° rotational intergrowth between adjacent flaky nanocrystals in the molecular sieve accounts for greater than or equal to 80%, preferably 80-100%. Using the aforementioned embodiment, the molecular sieve is more conducive to the diffusion of molecules when in use.

[0027] In the present invention, the structure of the ZSM-5 molecular sieve cross-assembled with sheet-like nanocrystals is determined by an X-ray diffraction spectrum (XRD), and the X-ray diffraction spectrum (XRD) is measured by an X-ray powder diffractometer. Before the sample test, a scanning electron microscope (SEM) is used to observe the crystallization of the molecular sieve sample to confirm that the sample contains only one crystal, that is, the molecular sieve sample is a pure phase, and then an XRD test is performed on this basis to ensure that there are no interference peaks of other crystals in the diffraction peaks in the XRD spectrum; during the test: the model of the molecular sieve X-ray powder diffractometer is a D / MAX 2550VB / PC X-ray powder diffractometer of Rigaku Company of Japan, which analyzes the physical phase of the sample, and a CuKα ray source is used. Nickel filter, 2θ scanning range 5-50°, operating voltage 40KV, current 20mA, scanning rate 10° / min.

[0028] According to the present invention, in some embodiments, the size of the agglomerate crystals is 0.5-3.0 μm, for example, 0.5 μm, 0.6 μm, 0.8 μm, 0.9 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.9 μm, 2.1 μm, 2.5 μm or 3.0 μm, preferably 0.6-2.5 μm. With the above embodiment, the molecular sieve is more conducive to the diffusion of molecules when used, and the molecular sieve structure has better stability.

[0029] According to the present invention, in some embodiments, the aspect ratio of the flaky nanocrystals is 1.2-2.5, such as 1.2, 1.5, 1.6, 1.7, 1.9, 2.0, 2.1, 2.3 or 2.5, preferably 1.2-2.0. With the above embodiment, the molecular sieve has good diffusivity.

[0030] According to the present invention, in some embodiments, the aspect ratio of the flaky nanocrystals is 4-20, for example, 4, 5, 5.6, 6.6, 7.3, 8, 8.3, 8.5, 9, 10, 11, 12, 13.8, 14.4, 15, 16, 17, 18, 19 or 20, preferably 4- 15. With the aforementioned embodiment, the molecular sieve has good diffusion performance and can show higher adsorption and catalytic performance.

[0031] According to the present invention, as long as the purpose of the present invention can be achieved, the length of the flaky nanocrystals is not particularly limited. In some preferred embodiments, the length of the flaky nanocrystals is 30-2500nm, for example, 30nm, 50nm, 60nm, 70nm, 78nm, 165nm, 230nm, 350nm, 450nm, 620nm, 640nm, 1000nm, 1500nm, 1800nm, 2000nm, 2200nm or 2500nm, preferably 30-2200nm. By adopting the above preferred embodiments, the molecular sieve has better diffusivity.

[0032] According to the present invention, as long as the purpose of the present invention can be achieved, the width of the flaky nanocrystals is not particularly limited. In some preferred embodiments, the width of the flaky nanocrystals is 20-1500nm, for example, 20nm, 30nm, 40nm, 50nm, 60nm, 110nm, 120nm, 200nm, 230nm, 330nm, 370nm, 500nm, 600nm, 800nm, 1000nm, 1100nm, 1300nm, 1400nm or 1500nm, preferably 20-1300nm. By adopting the aforementioned preferred embodiment, the molecular sieve has better diffusivity.

[0033] According to the present invention, as long as the purpose of the present invention can be achieved, the thickness of the flaky nanocrystals is not particularly limited. In some preferred embodiments, the thickness of the flaky nanocrystals is 5-150nm, for example, 5nm, 8nm, 10nm, 14nm, 15nm, 16nm, 25nm, 40nm, 75nm, 80nm, 100nm, 120nm, 130nm, 140nm or 150nm, preferably 8-130nm. By adopting the aforementioned preferred embodiment, the molecular sieve has better diffusivity.

[0034] In the present invention, the morphology and size of the plate-like nanocrystals and the agglomerate crystals can be observed from the scanning electron microscope image of the molecular sieve. In the present invention, the scanning electron microscope (SEM) used is the NOVA NanoSEM 450 field emission scanning electron microscope produced by FEI Company of the United States. When scanning, the molecular sieve is observed under a certain magnification of the scanning electron microscope, and an observation field of view is randomly selected to calculate the average length of all the flaky nanocrystals in the observation field of view, and the operation is repeated 10 times in total. The average value of the sum of the 10 times is taken as the length of the flaky nanocrystal. The width and thickness of all crystals in the observation field of view are measured in the same way, and the length of the agglomerate crystal is the size of the agglomerate crystal. The operation is repeated 5 times; and the proportion of the angles between adjacent flaky nanocrystals of 0-10°, 25-35° and 80-90° in the presidential count is counted, that is, the proportion of the agglomerate crystal morphology composed of cross-assembly of 90°±10° rotational symbiosis and 30°±5° rotational symbiosis in the total statistical number is counted, and the operation is repeated 5 times.

[0035] According to the present invention, as long as the purpose of the present invention can be achieved, the SiO 2 / Al 2 O 3 The molar ratio is not particularly limited. In some embodiments, the SiO 2 / Al 2 O 3 The molar ratio is greater than or equal to 20. The molecular sieve in the above-mentioned embodiment has good diffusion performance and a wide silicon-aluminum ratio window, and can be used as an adsorbent or a catalyst for organic compound conversion.

[0036] In the present invention, it is understood that the SiO 2 / Al 2 O 3 The molar ratio can be infinite. When it is infinite, it means that the ZSM-5 molecular sieve is a ZSM-5 molecular sieve of pure silicon, that is, Silicalite-1 molecular sieve.

[0037] In the present invention, the molecular sieve inductively coupled plasma atomic emission spectrometer (ICP) model is Varian 710-ES, and the analysis sample is dissolved with hydrofluoric acid to detect the content of the element in moles. SiO 2 / Al 2 O 3 When the molar ratio exceeds 1500, the molecular sieve can be considered to be composed of pure silicon.

[0038] According to the present invention, in some embodiments, the total specific surface area of ​​the ZSM-5 molecular sieve is not less than 450 m 2 / g. The molecular sieve in the above-mentioned embodiment has good molecular diffusion.

[0039] According to the present invention, in some preferred embodiments, the total specific surface area of ​​the ZSM-5 molecular sieve is 450-700 m 2 / g. The molecular sieve in the above-mentioned embodiment has good molecular diffusion.

[0040] According to the present invention, in some embodiments, the external specific surface area of ​​the ZSM-5 molecular sieve is not less than 60 m 2 / g. The molecular sieve in the above-mentioned embodiment has good diffusivity and stability.

[0041] According to the present invention, in some preferred embodiments, the external specific surface area of ​​the ZSM-5 molecular sieve is 60-200 m 2 / g. The molecular sieve in the above-mentioned embodiment has good diffusivity and stability.

[0042] According to the present invention, as long as the purpose of the present invention can be achieved, the total pore volume of the ZSM-5 molecular sieve is not particularly limited. In some embodiments, the total pore volume of the ZSM-5 molecular sieve is not less than 0.35 cm 3 / g. The molecular sieve in the above-mentioned embodiment has good diffusivity and adsorption.

[0043] According to the present invention, in some preferred embodiments, the total pore volume of the ZSM-5 molecular sieve is 0.35-0.60 cm 3 / g. The molecular sieve in the above-mentioned embodiment has good diffusivity and adsorption.

[0044] According to the present invention, in some embodiments, the micropore volume of the ZSM-5 molecular sieve is not less than 0.12 cm 3 / g. The molecular sieve in the above-mentioned embodiment has good diffusivity and adsorption.

[0045] According to the present invention, in some preferred embodiments, the micropore volume of the ZSM-5 molecular sieve is 0.12-0.24 cm 3 / g. The molecular sieve in the above-mentioned embodiment has good diffusivity and adsorption.

[0046] In the present invention, the total specific surface area, external specific surface area, total pore volume and micropore volume of the molecular sieve are measured by nitrogen physical adsorption and desorption method (BET method): the nitrogen physical adsorption and desorption isotherm of the molecular sieve is measured by a physical adsorption instrument (3H-2000PS4 type specific surface and pore size analyzer), and then calculated by the BET equation and the t-plot equation. The experimental conditions for the molecular sieve are: the measurement temperature is -196°C, and the molecular sieve is first heat-treated at 550°C in air atmosphere for 6 hours before measurement, and then vacuum-treated at 350°C for 4 hours.

[0047] The second aspect of the present invention provides a method for preparing the ZSM-5 molecular sieve according to the first aspect of the present invention, wherein the preparation method comprises: crystallizing a raw material mixture containing a silicon source in the presence of a structure directing agent,

[0048] Wherein, the structure directing agent contains a structural unit a represented by formula (1),

[0049]

[0050] In formula (1), X is a halogen ion or a hydroxide ion, and * represents a bonding site.

[0051] In the present invention, the polymer containing the structural unit a shown in formula (1) is used as the structure directing agent. The molecular sieve has a special morphology of agglomerate crystals composed of cross-assembly of sheet-like nanocrystals and has good diffusion performance.

[0052] According to the present invention, it can be understood that the structure directing agent containing the structural unit a shown in formula (1) is a polymer, wherein the polymer often exists in the form of a mixture, that is, a mixture of structure directing agents with different polymerization degrees (that is, different numbers of structural units a) containing the same structural unit a. In the present invention, the average polymerization degree of structural unit a refers to the average number of structural units a. In some embodiments, the average polymerization degree of the structure directing agent is 2-20, for example, 2, 3.9, 5.2, 6, 7, 8, 9.7, 11, 12, 13, 15, 18 or 20, preferably 3-12. By adopting the above-mentioned embodiment, a molecular sieve with a special morphology can be prepared, and the molecular sieve has good molecular diffusion.

[0053] In the present invention, [Pr 4 -6-6-(Y) 2 ] n represents the structure of the structure directing agent (SDA), wherein Y is OH or halogen, n is the average degree of polymerization, and the amount of the structure directing agent in the raw material system is the total molar amount of the structural unit a.

[0054] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the silicon source is not particularly limited. In some embodiments, the silicon source is provided in an amount of SiO 2 The molar amount of the silicon source and the structure directing agent is calculated based on the molar amount of the structural unit a, and the molar ratio of the silicon source to the structure directing agent is 1:(0.1-0.4), for example, 1:0.1, 1:0.16, 1:0.21, 1:0.28 or 1:0.3. The molecular sieve prepared by the above embodiment has good diffusion performance.

[0055] According to the present invention, it can be understood that the raw material mixture is obtained by mixing the raw material including the silicon source with the solvent. As long as the purpose of the present invention can be achieved, the amount of the solvent added is not particularly limited. In some embodiments, the silicon source is provided with SiO 2 In terms of molar amount, the molar ratio of the silicon source to the solvent in the raw material mixed solution is 1:(15-180).

[0056] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the solvent is not particularly limited. In the present invention, water is used as a solvent to illustrate the advantages of the present invention, but the present invention is not limited thereto.

[0057] According to the present invention, the silicon source is a raw material that can provide silicon dioxide. As long as the purpose of the present invention can be achieved, the specific type of the silicon source is not particularly limited. In some embodiments, the silicon source is selected from at least one of tetraethyl orthosilicate, fumed silica, silica sol and white carbon black.

[0058] According to the present invention, in some embodiments, the raw material mixed solution further contains an optional aluminum source.

[0059] According to the present invention, it is understandable that in other embodiments, no aluminum source may be used in the preparation process of the ZSM-5 molecular sieve of the present invention, and the prepared ZSM-5 molecular sieve is a pure silicon molecular sieve.

[0060] According to the present invention, when an aluminum source is used in the preparation process of the ZSM-5 molecular sieve of the present invention (i.e., when the raw material mixed solution contains an aluminum source), as long as the purpose of the present invention can be achieved, the amount of the aluminum source is not particularly limited. In some embodiments, the silicon source is provided in the form of SiO 2 The molar amount of aluminum source is to provide Al 2 O 3 The molar ratio of the silicon source to the aluminum source is 1:(0-0.05) and is not 0. By adopting the above-mentioned embodiment, a wider silicon-to-aluminum ratio window can be obtained.

[0061] According to the present invention, when an aluminum source is used in the preparation process of the ZSM-5 molecular sieve described in the present invention (i.e., when the raw material mixture contains an aluminum source), those skilled in the art can select the specific type of the optional aluminum source as needed. In some embodiments, the aluminum source is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium aluminate, pseudo-boehmite and aluminum isopropoxide.

[0062] According to the present invention, in some embodiments, the raw material mixture further contains an optional alkali source.

[0063] According to the present invention, it is understood that, in other embodiments, no alkali source may be used in the preparation process of the ZSM-5 molecular sieve of the present invention. When no alkali source is used, the generation of a large amount of waste liquid during the modification (e.g., hydrogen modification) of the prepared ZSM-5 molecular sieve can be avoided.

[0064] According to the present invention, when an alkali source is used in the preparation process of the ZSM-5 molecular sieve of the present invention (i.e., when the raw material mixture contains an alkali source), as long as the purpose of the present invention can be achieved, the amount of the alkali source is not particularly limited. In some embodiments, the silicon source is provided in the form of SiO 2 The molar amount of the silicon source is calculated based on the molar amount of the cation provided, and the molar ratio of the silicon source to the alkali source is 1:(0-0.3) and is not 0.

[0065] According to the present invention, when an alkali source is used in the preparation process of the ZSM-5 molecular sieve described in the present invention (i.e., when the raw material mixture contains an alkali source), those skilled in the art can select the specific type of the optional alkali source as needed. In some embodiments, the alkali source is selected from at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide.

[0066] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the crystallization treatment are not particularly limited. In some embodiments, the conditions of the crystallization treatment include: a crystallization temperature of 120-190° C., preferably 140-180° C. Using the above embodiment, the prepared molecular sieve has a special morphology and good diffusivity.

[0067] According to the present invention, in some embodiments, the crystallization treatment conditions include: the crystallization time is 2-15 days, preferably 3-14 days. Using the above embodiment, the prepared molecular sieve has a special morphology and good diffusivity.

[0068] According to the present invention, as long as the purpose of the present invention can be achieved, the crystallization process can be carried out under static conditions or under dynamic conditions. In this application, static crystallization conditions are used as an example to illustrate the advantages of the present invention, but the present invention is not limited to this.

[0069] According to the present invention, in some embodiments, the method for preparing ZSM-5 molecular sieve further comprises separation and calcination after crystallization treatment.

[0070] According to the present invention, separation after crystallization is to obtain a molecular sieve product, and the molecular sieve product can be obtained by any conventional separation method in the art, such as a separation method in which the mixture obtained by crystallization is filtered, washed and dried. Among them, filtering, washing and drying can be carried out in any conventional manner in the art. For example, when filtering, a simple suction filtration in the art can be used to obtain a product mixture; when washing, deionized water and / or ethanol can be used for washing; when drying, it can be carried out under normal pressure or under reduced pressure. Those skilled in the art can select appropriate drying time and drying temperature as needed, for example, the drying temperature is 40-250°C, preferably 60-150°C, and the drying time is 8-30 hours, preferably 10-20 hours.

[0071] According to the present invention, it can be understood by those skilled in the art that when the raw material for preparing the ZSM-5 molecular sieve does not contain alkali metal ions, the ZSM-5 molecular sieve that can be prepared by calcining after the crystallization treatment is a hydrogen-type ZSM-5 molecular sieve; when the raw material for preparing the ZSM-5 molecular sieve contains alkali metal ions, the ZSM-5 molecular sieve prepared by calcining after the crystallization treatment is a basic molecular sieve (such as a sodium-type ZSM-5 molecular sieve, a potassium-type ZSM-5 molecular sieve or a lithium-type ZSM-5 molecular sieve), wherein the calcination can be carried out in any manner conventionally known in the art, and in some embodiments, the calcination conditions include: being carried out in an oxygen-containing atmosphere, wherein the oxygen-containing atmosphere that can be listed includes an oxygen atmosphere or an air atmosphere; in some embodiments, the calcination conditions include: a calcination temperature of 300-800°C, preferably 400-650°C; in some embodiments, the calcination conditions include: a calcination time of 1-10 hours, preferably 3-6 hours.

[0072] The third aspect of the present invention provides the use of the ZSM-5 molecular sieve described in the first aspect of the present invention in adsorption treatment and / or organic compound conversion reaction.

[0073] In the present invention, the ZSM-5 molecular sieve with a specific morphology has a higher adsorption capacity and use stability for organic molecules, and has good catalytic performance in the conversion reaction of organic compounds.

[0074] According to the present invention, the ZSM-5 molecular sieve in the present invention may be involved in any method of organic compound conversion reaction. In some preferred embodiments, the organic compound conversion reaction includes isomerization reaction of olefins, catalytic cracking reaction of one or more of isopropylbenzene, diisopropylbenzene, triisopropylbenzene and Beckmann rearrangement reaction of cyclohexanone oxime to produce caprolactam.

[0075] In the present invention, those skilled in the art can select pure silicon type ZSM-5 molecular sieve or silicon-aluminum type ZSM-5 molecular sieve for application as needed, for example, using pure silicon type ZSM-5 molecular sieve for Beckmann rearrangement to produce caprolactam reaction, or using silicon-aluminum type ZSM-5 molecular sieve for catalytic cracking reaction of isopropylbenzene, diisopropylbenzene and triisopropylbenzene.

[0076] In the present invention, those skilled in the art can select the form of the ZSM-5 molecular sieve when it is used as needed. In some embodiments, it can be used in any physical form, such as powder, granular, or prepared into a molded product (such as strips, clover, etc.) using a binder. These physical forms can be obtained in any conventional manner known in the art without particular limitation; in other embodiments, the ZSM-5 molecular sieve can be modified according to conventional methods in the art and then used. For example, when the ZSM-5 molecular sieve is an alkaline molecular sieve (such as a sodium ZSM-5 molecular sieve, a potassium ZSM-5 molecular sieve, or a lithium ZSM-5 molecular sieve), it can be modified to a hydrogen form to obtain a hydrogen ZSM-5 molecular sieve, and then used in the form of a hydrogen ZSM-5 molecular sieve.

[0077] According to the present invention, the basic molecular sieve (such as sodium ZSM-5 molecular sieve, potassium ZSM-5 molecular sieve or lithium ZSM-5 molecular sieve) can be modified to hydrogen form using conventional methods in the art. In some embodiments, the basic molecular sieve is ammonium exchanged with an ammonium salt solution, and then washed, dried and calcined to prepare a hydrogen ZSM-5 molecular sieve.

[0078] In the present invention, the ammonium salt solution refers to a solution obtained by mixing an ammonium salt with water.

[0079] According to the present invention, in some embodiments, the ammonium salt in the ammonium salt solution is selected from at least one of ammonium chloride, ammonium nitrate, ammonium carbonate and ammonium sulfate.

[0080] According to the present invention, in some embodiments, the ammonium ion concentration in the ammonium salt solution is 0.1-1.0 mol / L.

[0081] According to the present invention, in some embodiments, the solid-liquid ratio (mass ratio) of the basic molecular sieve (such as sodium ZSM-5 molecular sieve, potassium ZSM-5 molecular sieve or lithium ZSM-5 molecular sieve) to the ammonium salt solution is 1: (5-20).

[0082] According to the present invention, the number of ammonium exchanges can be selected as needed, generally greater than or equal to 1 time; the conditions for ammonium exchange are not particularly limited, for example, ammonium ion exchange is performed at 55-75° C. for 1-5 hours.

[0083] According to the present invention, washing, drying and calcination are performed after ammonium exchange, wherein washing is a conventional washing method in the art, such as centrifugal washing; the drying method can be a conventional drying method in the art, such as drying overnight at 90-110°C; the calcination method can be a conventional calcination method in the art, such as calcining in air at 500-600°C for 3-6 hours.

[0084] In the present invention, the time of "overnight drying" is 10-16 hours.

[0085] The fourth aspect of the present invention provides a method for catalytic cracking of triisopropylbenzene, wherein the method comprises: in the presence of the ZSM-5 molecular sieve described in the first aspect of the present invention and / or the hydrogen-type ZSM-5 molecular sieve after hydrogen-modification of the ZSM-5 molecular sieve described in the first aspect of the present invention as an active component, triisopropylbenzene is subjected to a catalytic cracking reaction.

[0086] In the present invention, the ZSM-5 molecular sieve and / or the hydrogen-modified ZSM-5 molecular sieve in the present invention is used for catalytic cracking of triisopropylbenzene, and triisopropylbenzene has a better conversion rate and the product benzene has good selectivity.

[0087] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the catalytic cracking reaction are not particularly limited. In some embodiments, the conditions of the catalytic cracking reaction include: a reaction temperature of 270-350°C.

[0088] According to the present invention, in some embodiments, the conditions of the catalytic cracking reaction include: a weight space velocity of triisopropylbenzene of 3-6h -1 .

[0089] According to the present invention, the reaction time of the catalytic cracking reaction can be selected as required, for example, 8-20 hours.

[0090] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:

[0091] The method for catalytic cracking of triisopropylbenzene is as follows: under the action of a catalyst, triisopropylbenzene undergoes a catalytic cracking reaction, and the conditions for the catalytic cracking reaction are as follows: a reaction temperature of 270-350°C and a space velocity of 3-6h -1 , the reaction time is 10-15h.

[0092] Conversion rate of triisopropylbenzene (%) = (molar amount of feed triisopropylbenzene - molar amount of triisopropylbenzene in product) / (molar amount of feed triisopropylbenzene) × 100%.

[0093] Benzene selectivity % = (molar amount of benzene in the product) / (total molar amount of aromatic hydrocarbons in the product)×100%; wherein the aromatic hydrocarbons in the product do not include the raw material triisopropylbenzene.

[0094] The method for preparing caprolactam by Beckmann rearrangement of cyclohexanone oxime is as follows: cyclohexanone is subjected to Beckmann rearrangement reaction in a solvent under the action of a catalyst, and the reaction conditions are as follows: pure silicon ZSM-5 molecular sieve is used as a catalyst, 5wt% cyclohexanone oxime-ethanol solution, reaction temperature is 300-400°C, and space velocity is 3-6h -1 .

[0095] The conversion rate of cyclohexanone oxime (%) = (the molar amount of cyclohexanone oxime fed - the molar amount of cyclohexanone oxime in the product) / (the molar amount of cyclohexanone oxime fed) × 100%.

[0096] Caprolactam selectivity % = (mass of caprolactam in the product) / (total mass of the product) x 100%; wherein unreacted cyclohexanone oxime and solvent ethanol in the raw material are not considered in the product.

[0097] Example 1

[0098] 13.50 g of deionized water, 0.42 g of [Pr 4 -6-6-(OH) 2 ] 3.9 (SDA), 0.008 g of sodium aluminate, and 1.04 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:

[0099] SiO 2 / Al 2 O 3 =102;

[0100] NaOH / SiO 2 =0.02;

[0101] SDA / SiO 2 =0.21;

[0102] H 2 O / SiO 2 =150;

[0103] The mixture was placed in a stainless steel reactor and heated for crystallization at 165°C for 13 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0104] Figure 1 is the X-ray diffraction pattern of the molecular sieve sample. Figure 1 The molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0105] From the SEM image of the molecular sieve sample, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 84%; the thickness of the flaky nanocrystals is 10nm, the length is 50nm, the width is 30nm, the aspect ratio is 5, the aspect ratio is 1.7, and the size of the agglomerate crystal is 0.8μm.

[0106] The SiO content of the molecular sieve samples was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 Molar ratio 76.

[0107] N of molecular sieve samples 2 Physical adsorption diagram Figure 2 As shown, through Figure 2 It can be calculated that the specific surface area of ​​the molecular sieve sample is 628 m 2 / g, the external specific surface area measured by BET method is 158 m 2 / g; total pore volume 0.39 cm 3 / g, micropore volume is 0.20 cm 3 / gram.

[0108] ZSM-5 molecular sieve was mixed with 0.2 mol / L NH 4 NO 3 The solution (mass ratio 1:20) was subjected to ammonium ion exchange at 65°C for 3 hours, and then centrifuged and washed. The ammonium ion exchange and centrifugal washing were repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain the hydrogen-type ZSM-5 molecular sieve.

[0109] The catalytic cracking reaction of triisopropylbenzene was carried out using hydrogen-type ZSM-5 molecular sieve as a catalyst, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0110] Example 2

[0111] 13.50 g of deionized water, 0.32 g of [Pr 4 -6-6-(OH) 2 ] 3.9 (SDA), 0.008 g of sodium aluminate, and 1.04 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:

[0112] SiO 2 / Al 2O 3 =102;

[0113] NaOH / SiO 2 =0.02;

[0114] SDA / SiO 2 =0.16;

[0115] H 2 O / SiO 2 =150;

[0116] The mixture was placed in a stainless steel reactor and heated for crystallization at 165°C for 12 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0117] Figure 3 is the X-ray diffraction pattern of the molecular sieve sample. Figure 3 The molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0118] From the SEM image of the molecular sieve sample, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 88%; the thickness of the flaky nanocrystals is 14nm, the length is 78nm, the width is 40nm, the aspect ratio is 5.6, the aspect ratio is 2.0, and the size of the agglomerate crystal is 1.3μm.

[0119] The SiO content of the molecular sieve samples was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 Molar ratio 72.

[0120] N of molecular sieve samples 2 Physical adsorption diagram and Figure 2 Similarly, the specific surface area of ​​molecular sieve is 596 m 2 / g, the external specific surface area measured by BET method is 102 m 2 / g; total pore volume 0.39 cm 3 / g, micropore volume is 0.20 cm 3 / gram.

[0121] ZSM-5 molecular sieve was mixed with 0.2 mol / L NH 4 NO 3The solution (mass ratio 1:20) was subjected to ammonium ion exchange at 65°C for 3 hours and then centrifuged for washing. The ammonium ion exchange and centrifugal washing were repeated twice and the obtained sample was dried at 100°C overnight and then calcined in air at 550°C for 4 hours to obtain a hydrogen-type ZSM-5 molecular sieve sample.

[0122] The catalytic cracking reaction of triisopropylbenzene was carried out using hydrogen-type ZSM-5 molecular sieve as a catalyst, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0123] Example 3

[0124] 13.50 g of deionized water, 0.42 g of [Pr 4 -6-6-(OH) 2 ] 3.9 (SDA), 0.008 g of aluminum hydroxide, and 1.04 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:

[0125] SiO 2 / Al 2 O 3 =97;

[0126] SDA / SiO 2 =0.21;

[0127] H2O / SiO 2 =150.

[0128] The mixture was placed in a stainless steel reactor and heated for crystallization at 165°C for 14 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0129] Figure 4 is the X-ray diffraction pattern of the molecular sieve sample. Figure 4 The molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0130] Figure 5 This is the SEM image of the molecular sieve sample. Through the SEM image of the molecular sieve sample, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals with 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 92%; the thickness of the flaky nanocrystals is 80nm, the length is 640nm, the width is 330nm, the aspect ratio is 8.0, the aspect ratio is 1.9, and the size of the agglomerate crystal is 0.8μm.

[0131] The SiO content of the molecular sieve samples was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 Molar ratio 92.

[0132] N of molecular sieve samples 2 Physical adsorption diagram and Figure 2 Similarly, the surface area of ​​the molecular sieve sample is 614 m 2 / g, the external specific surface area measured by BET method is 124 m 2 / g; total pore volume 0.38 cm 3 / g, micropore volume is 0.19 cm 3 / gram.

[0133] The molecular sieve sample was used as a catalyst to carry out a catalytic cracking reaction of triisopropylbenzene, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0134] Example 4

[0135] 26.10 g of deionized water, 0.84 g [Pr 4 -6-6-(OH) 2 ] 3.9 (SDA), 0.19 g of sodium hydroxide aqueous solution (30% mass concentration), 0.008 g of sodium aluminate, and 2.08 g of ethyl orthosilicate were stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture was:

[0136] SiO 2 / Al 2 O 3 =204;

[0137] NaOH / SiO 2 =0.15;

[0138] SDA / SiO 2 =0.21;

[0139] H 2 O / SiO 2 =146;

[0140] The mixture was placed in a stainless steel reactor and heated for crystallization at 160°C for 7 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0141] Figure 6 is the X-ray diffraction pattern of the molecular sieve sample. Figure 6 The molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0142] From the SEM image of the molecular sieve sample, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 86%; the thickness of the flaky nanocrystals is 16nm, the length is 230nm, the width is 120nm, the aspect ratio is 14.4, the aspect ratio is 1.9, and the size of the agglomerate crystal is 0.9μm.

[0143] The SiO content of the molecular sieve samples was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 Molar ratio 183.

[0144] N of molecular sieve samples 2 Physical adsorption diagram and Figure 2 Similarly, the molecular sieve sample has a surface area of ​​596 m 2 / g, the external specific surface area measured by BET method is 112 m 2 / g; total pore volume 0.42 cm 3 / g, micropore volume is 0.20 cm 3 / gram.

[0145] ZSM-5 molecular sieve was mixed with 0.2 mol / L NH 4 NO 3 The solution (mass ratio 1:20) was subjected to ammonium ion exchange at 65°C for 3 hours, and then centrifuged and washed. The ammonium ion exchange and centrifugal washing were repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain the hydrogen-type ZSM-5 molecular sieve.

[0146] The catalytic cracking reaction of triisopropylbenzene was carried out using hydrogen-type ZSM-5 molecular sieve as a catalyst, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0147] Example 5

[0148] 13.50 g of deionized water, 0.42 g of [Pr 4 -6-6-(OH) 2 ] 3.9 (SDA), 1.04 g of ethyl orthosilicate, and stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture is:

[0149] SDA / SiO 2 =0.21;

[0150] H 2 O / SiO2 =150;

[0151] The mixture was placed in a stainless steel reactor and heated for crystallization at 160°C for 8 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0152] Figure 7 is the X-ray diffraction pattern of the molecular sieve sample. Figure 7 The molecular sieve sample that can be obtained is ZSM-5 (Silicalite-1) molecular sieve of pure silicon.

[0153] Figure 8 This is the SEM image of the molecular sieve sample. Through the SEM image of the molecular sieve sample, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals with 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 89%; the thickness is 130nm, the length is 1800nm, the width is 1100nm, the aspect ratio is 13.8, the aspect ratio is 1.6, and the size of the agglomerate crystal is 2.1μm.

[0154] The SiO content of the molecular sieve samples was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 The molar ratio is greater than 2000, which is pure silicon ZSM-5 molecular sieve.

[0155] N of molecular sieve samples 2 Physical adsorption diagram and Figure 2 Similarly, the molecular sieve sample has a surface area of ​​584 m 2 / g, the external specific surface area measured by BET method is 106 m 2 / g; total pore volume 0.42 cm 3 / g, micropore volume is 0.19 cm 3 / gram.

[0156] The molecular sieve sample was used as a catalyst for the Beckmann rearrangement reaction of cyclohexanone oxime, wherein the reaction conditions were: 5wt% cyclohexanone oxime-ethanol solution, reaction temperature of 370°C, space velocity of 3.5h -1 , the conversion of cyclohexanone oxime was 93% and the selectivity of caprolactam was 95%.

[0157] Example 6

[0158] 13.05 g of deionized water, 0.42 g of [Pr 4 -6-6-(OH)2 ] 5.2 (SDA), 0.03 g of sodium aluminate, 0.09 g of sodium hydroxide aqueous solution (30% mass concentration), 1.04 g of ethyl orthosilicate, and stirred at room temperature for 24 hours to obtain a mixture. The final molar ratio of the mixture is:

[0159] SiO 2 / Al 2 O 3 =27;

[0160] NaOH / SiO 2 =0.20;

[0161] SDA / SiO 2 =0.21;

[0162] H 2 O / SiO 2 =145.

[0163] The mixture was placed in a stainless steel reactor and heated for crystallization at 170°C for 5 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0164] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0165] From the SEM image of the molecular sieve sample, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 83%; the thickness of the flaky nanocrystals is 75nm, the length is 620nm, the width is 370nm, the aspect ratio is 8.3, the aspect ratio is 1.7, and the size of the agglomerate crystal is 1.9μm.

[0166] The SiO content of the molecular sieve samples was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 Molar ratio 25.

[0167] N of molecular sieve samples 2 Physical adsorption diagram and Figure 2 Similarly, the molecular sieve sample has a specific surface area of ​​586 m 2 / g, the external specific surface area measured by BET method is 137 m 2 / g; total pore volume 0.43 cm 3 / g, micropore volume is 0.20 cm 3 / gram.

[0168] ZSM-5 molecular sieve was mixed with 0.2 mol / L NH 4 NO 3 The solution (mass ratio 1:20) was subjected to ammonium ion exchange at 65°C for 3 hours, and then centrifuged and washed. The ammonium ion exchange and centrifuged and washed were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain the hydrogen-type ZSM-5 molecular sieve.

[0169] The catalytic cracking reaction of triisopropylbenzene was carried out using hydrogen-type ZSM-5 molecular sieve as a catalyst, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0170] Example 7

[0171] A mixture was prepared according to the method of Example 1, except that [Pr 4 -6-6-Br 2 ] 9.7 Replace [Pr 4 -6-6-(OH) 2 ] 3.9 , and the amount of each raw material added is controlled so that the molar ratio of the final mixture is:

[0172] SiO 2 / Al 2 O 3 =50;

[0173] NaOH / SiO 2 =0.15;

[0174] SDA / SiO 2 =0.21;

[0175] H 2 O / SiO 2 =25;

[0176] The mixture was placed in a stainless steel reactor and heated for crystallization at 175°C for 4 days under static crystallization conditions. After the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.

[0177] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0178] SEM images of molecular sieve samples and Figure 2Similarly, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals with 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 86%; the thickness of the flaky nanocrystals is 15nm, the length is 60nm, the width is 40nm, the aspect ratio is 4.0, the aspect ratio is 1.5, and the size of the agglomerate crystal is 1.2μm.

[0179] The SiO2 content of the molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 Molar ratio 45.

[0180] N of molecular sieve samples 2 Physical adsorption diagram and Figure 2 Similarly, the surface area of ​​the molecular sieve sample is 620 m 2 / g, the external specific surface area measured by BET method is 146 m 2 / g; total pore volume 0.37 cm 3 / g, micropore volume is 0.19 cm 3 / gram.

[0181] ZSM-5 molecular sieve was mixed with 0.2 mol / L NH 4 NO 3 The solution (mass ratio 1:20) was subjected to ammonium ion exchange at 65°C for 3 hours, and then centrifuged and washed. The ammonium ion exchange and centrifuged and washed were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain the hydrogen-type ZSM-5 molecular sieve.

[0182] The catalytic cracking reaction of triisopropylbenzene was carried out using hydrogen-type ZSM-5 molecular sieve as a catalyst, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0183] Example 8

[0184] A mixture was prepared according to the method of Example 1, except that silica sol (40% mass concentration) was used to replace ethyl orthosilicate, and the addition amount of each raw material was controlled so that the molar ratio of the final mixture was the same as that of Example 1.

[0185] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0186] SEM images of molecular sieve samples and Figure 2Similarly, it can be obtained that the molecular sieve sample has an agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals, and the number of agglomerate crystal morphology composed of cross-assembly of flaky nanocrystals with 90°±10° rotational symbiosis and 30°±5° rotational symbiosis between adjacent flaky nanocrystals in the molecular sieve sample accounts for 86%; the thickness of the flaky nanocrystals is 25nm, the length is 165nm, the width is 110nm, the aspect ratio is 6.6, the aspect ratio is 1.5, and the size of the agglomerate crystal is 1.4μm.

[0187] The SiO2 content of the molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP). 2 / Al 2 O 3 Molar ratio 88.

[0188] N of molecular sieve samples 2 Physical adsorption diagram and Figure 2 Similarly, the molecular sieve sample has a surface area of ​​628 m 2 / g, the external specific surface area measured by BET method is 151 m 2 / g; total pore volume 0.40 cm 3 / g, micropore volume is 0.18 cm 3 / gram.

[0189] ZSM-5 molecular sieve was mixed with 0.2 mol / L NH 4 NO 3 The solution (mass ratio 1:20) was subjected to ammonium ion exchange at 65°C for 3 hours, and then centrifuged and washed. The ammonium ion exchange and centrifuged and washed were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain the hydrogen-type ZSM-5 molecular sieve.

[0190] The catalytic cracking reaction of triisopropylbenzene was carried out using hydrogen-type ZSM-5 molecular sieve as a catalyst, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0191] Comparative Example 1

[0192] A mixture was prepared according to the method of Example 5, except that tetrapropylammonium hydroxide aqueous solution (25% mass concentration) (SDA) was used instead of [Pr 4 -6-6-(OH) 2 ] 3.9 , and the amount of each raw material added is controlled so that the molar ratio of the final mixture is the same as that of Example 5.

[0193] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as ZSM-5 (Silicalite-1) molecular sieve which is pure silicon.

[0194] The SEM images of the molecular sieve samples are shown in Fig. 9 As shown, the molecular sieve sample has a chess piece-like morphology and does not have the crystal morphology of an aggregate composed of cross-assembly of 90°±10° rotational symbiosis and 30°±5° rotational symbiosis sheet-like nanocrystals.

[0195] The molecular sieve sample was used as a catalyst for the Beckmann rearrangement reaction of cyclohexanone oxime, wherein the reaction conditions were: 5wt% cyclohexanone oxime-ethanol solution, reaction temperature of 370°C, space velocity of 3.5h -1 , the conversion of cyclohexanone oxime was 79% and the selectivity of caprolactam was 84%.

[0196] Comparative Example 2

[0197] A mixture was prepared according to the method of Example 1, except that tetrapropylammonium hydroxide aqueous solution (25% mass concentration) (SDA) was used instead of [Pr 4 -6-6-(OH) 2 ] 3.9 , and the amount of each raw material added is controlled so that the molar ratio of the final mixture is the same as that of Example 7.

[0198] X-ray diffraction patterns of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample that can be obtained is ZSM-5 molecular sieve.

[0199] The SEM images of the molecular sieve samples are shown in Fig.10 As shown, the molecular sieve sample has a large grain morphology, and does not have the crystal morphology of agglomerates composed of cross-assembly of 90°±10° rotational intergrowth and 30°±5° rotational intergrowth sheet-like nanocrystals.

[0200] ZSM-5 molecular sieve was mixed with 0.2 mol / L NH 4 NO 3 The solution (mass ratio 1:20) was subjected to ammonium ion exchange at 65°C for 3 hours, and then centrifuged and washed. The ammonium ion exchange and centrifuged and washed were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain the hydrogen-type ZSM-5 molecular sieve.

[0201] The catalytic cracking reaction of triisopropylbenzene was carried out using hydrogen-type ZSM-5 molecular sieve as a catalyst, wherein the conditions and reaction results of the catalytic cracking reaction are shown in Table 1.

[0202] Table 1

[0203]

[0204] It can be seen from the results in the examples and comparative examples that the use of the ZSM-5 molecular sieve of the present invention as a catalyst for the catalytic cracking of triisopropylbenzene and the Beckmann rearrangement of cyclohexanone oxime to prepare caprolactam has significantly better effects.

[0205] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A ZSM-5 molecular sieve, characterized in that: The ZSM-5 molecular sieve has an aggregate crystal morphology formed by cross-assembly of flaky nanocrystals, and adjacent flaky nanocrystals in the molecular sieve have an aggregate crystal morphology formed by cross-assembly of flaky nanocrystals with 90°±10° rotational intergrowth and 30°±5° rotational intergrowth.

2. The ZSM-5 molecular sieve according to claim 1, wherein The number of adjacent flaky nanocrystals in the molecular sieve having a crystal morphology of agglomerates composed of cross-assembly of flaky nanocrystals intergrown at 90°±10° rotation and intergrown at 30°±5° rotation accounts for greater than or equal to 80%, preferably 80-100%; and / or The size of the agglomerate crystals is 0.5-3.0 μm, preferably 0.6-2.5 μm; and / or The aspect ratio of the plate-like nanocrystals is 1.2-2.5, preferably 1.2-2.0; and / or The aspect ratio of the plate-like nanocrystals is 4-20, preferably 4-15; Preferably, The length of the plate-like nanocrystals is 30-2500 nm, preferably 30-2200 nm; and / or The width of the plate-like nanocrystals is 20-1500 nm, preferably 20-1300 nm; and / or The thickness of the plate-like nanocrystals is 5-150 nm, preferably 8-130 nm.

3. The ZSM-5 molecular sieve according to claim 1 or 2, wherein The SiO2 / Al2O3 molar ratio of the ZSM-5 molecular sieve is greater than or equal to 20; and / or The total specific surface area of ​​the ZSM-5 molecular sieve is not less than 450 m 2 / g, preferably 450-700 m 2 / g; and / or The external specific surface area of ​​the ZSM-5 molecular sieve is not less than 60 m 2 / g, preferably 60-200 m 2 / gram.

4. The ZSM-5 molecular sieve according to any one of claims 1 to 3, wherein The total pore volume of the ZSM-5 molecular sieve is not less than 0.35 cm 3 / g, preferably 0.35-0.60 cm 3 / g; and / or The micropore volume of the ZSM-5 molecular sieve is not less than 0.12 cm 3 / g, preferably 0.12-0.24 cm 3 / gram.

5. A method for preparing the ZSM-5 molecular sieve according to any one of claims 1 to 4, characterized in that: The preparation method comprises: in the presence of a structure directing agent, performing a crystallization treatment on a raw material mixed solution containing a silicon source, Wherein, the structure directing agent contains a structural unit a represented by formula (1), In formula (1), X is a halogen ion or a hydroxide ion, and * represents a bonding site.

6. The preparation method according to claim 5, wherein: The average degree of polymerization of the structure directing agent is 2-20, preferably 3-12; and / or The silicon source is calculated based on the molar amount of SiO2 provided, and the structure directing agent is calculated based on the molar amount of structural unit a, and the molar ratio of the silicon source to the structure directing agent is 1:(0.1-0.3); and / or The molar ratio of the silicon source to the solvent in the raw material mixture is 1:(15-180) based on the molar amount of SiO2 provided; and / or; The silicon source is selected from at least one of tetraethyl orthosilicate, fumed silica, silica sol and white carbon black.

7. The preparation method according to claim 5 or 6, wherein: The raw material mixture also contains an optional aluminum source and / or an alkali source; Preferably, When the raw material mixed solution contains an aluminum source, the silicon source is calculated in molar amount to provide SiO2, and the aluminum source is calculated in molar amount to provide Al2O3, and the molar ratio of the silicon source to the aluminum source is 1:(0-0.05) and is not 0; and / or When the raw material mixture contains an alkali source, the silicon source is calculated based on the molar amount of SiO2 provided, and the alkali source is calculated based on the molar amount of cations provided, and the molar ratio of the silicon source to the alkali source is 1:(0-0.3) and is not 0; and / or When the raw material mixture contains an aluminum source, the aluminum source is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, sodium metaaluminate, pseudo-boehmite and aluminum isopropoxide; and / or When the raw material mixed solution contains an aluminum source, the alkali source is selected from at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide.

8. The preparation method according to any one of claims 5 to 7, wherein: The conditions of the crystallization treatment include: The crystallization temperature is 120-190°C, preferably 140-180°C; and / or The crystallization time is 2-15 days, preferably 3-14 days.

9. The preparation method according to any one of claims 5 to 8, wherein: The preparation method also includes separation and calcination after the crystallization treatment; Preferably, the calcination conditions include: carried out under an oxygen-containing atmosphere; and / or The calcination temperature is 300-800°C, preferably 400-650°C; and / or The calcination time is 1-10 hours, preferably 3-6 hours.

10. Use of the ZSM-5 molecular sieve according to any one of claims 1 to 4 in adsorption treatment and / or organic compound conversion reaction; Preferably, the organic compound conversion reaction includes an isomerization reaction of olefins, a catalytic cracking reaction of one or more of isopropylbenzene, diisopropylbenzene and triisopropylbenzene, and a Beckmann rearrangement reaction of cyclohexanone oxime to produce caprolactam.

11. A method for catalytic cracking of triisopropylbenzene, characterized in that: The method includes: In the presence of the ZSM-5 molecular sieve described in any one of claims 1 to 4 and / or the hydrogen-modified ZSM-5 molecular sieve described in any one of claims 1 to 4 as an active component, triisopropylbenzene is subjected to a catalytic cracking reaction.

12. The method according to claim 11, wherein: The conditions of the catalytic cracking reaction include: The reaction temperature is 270-350°C; and / or The weight space velocity of triisopropylbenzene is 3-6h -1 .

Citation Information

Patent Citations

  • Mesoporous and microporous MFI type nano molecular sieve with flaky pastry-shaped morphology and preparation method and application thereof

    CN108002402A

  • Preparation method of mesoporous-microporous dual pore ZSM-5 zeolite nano sheet

    CN109205642A

  • Method for preparing hierarchical pore ZSM-5 molecular sieve with special morphology by using cheap commercially available organic amine

    CN113353952A